Das Steininschriftenprojekt des Wolkenheimklosters während der Liao-Dynastie (907-1125). Eine Analyse seiner Kolophone The stone sutra project of the Cloud Dwelling Monastery during the Liao Dynasty (907-1125). An analysis of its colophons - Chuang, Hui-Ping (Materiale Textkulturen [Material Text Cultures], 2018)
Between 616 and 1180, Buddhist monks at the Cloud Dwelling Monastery engraved around 1,600 sutras on 15,000 stone slabs to save the texts from the impending end of the world. Over one-third of text was inscribed during the Liao Dynasty. Through the analysis of the colophons, this volume offers insight into politics, society, and Buddhism during this period.